Evaluating the sophisticated digital assets and cryptocurrencies capacities of substituting international currencies in inflationary eras - Dimitriadis, Konstantinos; Koursaros, Demetris; Savva, Christos S. (My University, 2024)
This study investigates the dynamic nexus that major international currencies (US dollar, Euro, Japanese yen) exhibit with cryptocurrencies and highly innovative digital money (DeFi and NFT assets) during inflationary periods such as the Russia-Ukraine conflict (from 14 December 2021 until 1 March 2024). The Quantile Vector Autoregressive methodology as in Cunado et al. (2023) and daily data are adopted to investigate the net joint extended dynamic connectedness and network connectedness at lower and upper quantiles. Conventional international currencies act as hedgers against shocks while major cryptocurrencies are only modest generators with Ripple being an influential absorber of effects. DeFi mainly serve for counteracting losses from conventional investments in bear or bull markets and Maker is the most prominent generator of spillovers while NFTs mostly rely on a few very strong leaders –Gala being by far the strongest- to have an impact, imitating Bitcoin in the early cryptocurrency era.
Keywords: Dynamic connectedness; Non-Fungible Tokens; Decetralized Finance; Euro; US dollar